The treatment of constipation with herbal laxatives - Nedeljković Katarina; Kundaković Tatjana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Constipation is usual health problem that affects about a quarter of the population. Treatment of constipation remains a challenge because of multiple, multifaceted aetiology and individual response of each patient. The elimination of the constipation significantly improves the quality of life. There is a wide range of herbal remedies that can be used in therapy. The first recommendation in the treatment of constipation should be a diet that contains indigestible fibres with adequate fluid intake and encouragement of physical activity. The laxatives of synthetic or natural origin could be used in the therapy of constipation. Today, the three most important groups of herbal medicines are bulk-producing, osmotic and stimulant laxatives. The most significant bulk-producing laxatives are flaxseed (Lini semen), ispaghula seed and husk (Plantaginis ovatae semen et tegumentum), and psyllium seed (Psyllii semen). Antraquinone drugs are classified in the group of stimulant laxative. Because of the potential habituation, stimulating laxatives should not be used continuously over a long treatment period. In the treatment of chronic constipation are commonly used osmotic laxatives such as fruit of the black mulberry (Mori nigri fructus), figs (Fici fructus), fruit of tamarind (Tamarindi fructus) and Manna. All laxatives are effective but side effects are different from preparation to preparation.